Modification of the Diffusion Model As A Result of a New Variant Celebrity Endorsement - O. Addo, Jacob (British Journal of Marketing Studies, 2016)
This paper reports on findings from a research project that reflected upon the effectiveness of Celebrity endorsement (CE) and how it impacts on adoption. The study was undertaken to reflect upon the rate at which CE with the aid of modern technology have enhanced and transformed social interactions which have quickened communication within, between and among societies hence spreading information faster and easier throughout communities earlier than anticipated. The Rogers’ Diffusion and Adoption Model was applied to capture Customers and Business Executives experiences on using Celebrity Endorsers which provided a basis for observation and reflection. The research adopted both quantitative and qualitative methodology. Questionnaires were used to collect the data. The study surveyed 1000 Customers, and interviewed 30 Business Executives. The outcome of the study has proved that CE greatly impact on the diffusion process of products and services into markets at a faster rate than has been assumed. Hence it has modified the Rogers and Bass Diffusion model in 1983.